Pengembangan Komik Digital Berbasis Segitiga Restitusi untuk Meningkatkan Kemampuan Bernalar Kritis dan Karakter Mandiri Siswa Sekolah Dasar - Ni Wayan Asri Udayani; Sukardi Sukardi; Moh Irawan Zain (CV. Global Cendekia Inti, 2026)
This study was motivated by the need to develop innovative instructional media that integrate character education with digital technology at the elementary school level. A digital comic based on the Restitution Triangle was designed to address students' limited critical reasoning skills and low learning autonomy, which often rely on external control. By presenting reflective restitution-based scenarios, the media encourages students to evaluate their actions and develop intrinsic motivation for learning. This study aimed to develop a digital comic that meets the criteria of validity, practicality, and effectiveness in improving the critical reasoning skills and independent character of fifth-grade students at SDN 4 Terara. The study employed a Research and Development (R&D) approach using the 4D model (Define, Design, Develop, and Disseminate). Data were collected through expert validation, user response questionnaires, and field testing using a pretest-posttest control group design. The findings indicate that the developed media is highly valid, highly practical, and significantly effective in enhancing students' critical reasoning and independence, as confirmed by the t-test results (p = 0.001 < 0.05). Therefore, the Restitution Triangle-based digital comic is a feasible and effective instructional medium for fostering the Pancasila Student Profile through a reflective positive discipline approach.